(untitled) - McCullough, Susan (Hoboken, NJ, 2004)
This friendly guide provides reassuring, positive advice on handling the physical and emotional issues involved in caring for your beloved companion. You'll see how aging affects your dog, how to cope with common ailments, and what you can do to help your senior live a joyful, high-quality life. Discover how to: * Meet your senior's dietary needs * Safely exercise your senior * Manage health costs * Teach an older dog new tricks * Gain inspiration from stories about super senior dogs.
Keywords: Dogs,Dogs,Veterinary geriatrics,Chó,Chó,Lão khoa về thú y; Aging,Diseases,Lão hóa,Bệnh